Collective portrait of head of Omsk school for training infantry warrant officers - A. Yu. Sablin (Омский научный вестник: Серия "Общество. История. Современность")
In the article, on the basis of the prosopographic method, the collective portrait of the head of Omsk schools for the training of infantry warrant officers is reconstructed. The study is based on army clerical records from the Russian State Military Historical Archive and the Historical Archive of the Omsk Region. As a result of the study, it is found that the head of Omsk school for training infantry warrant officers, as a rule, is a nobleman, of the Orthodox faith, a combat officer with the rank of staff captain to lieutenant general, who has experience of direct participation in hostilitie